The Influence Of PowerPoint-Based Use In Increasing Learning Attention Student On Class X SMAN 10 Padang - Raysa Juwita; Mades Fifendy; Ardi Ardi; Heffi Alberida (Universitas Negeri Padang, 2019)
This research is based on the problems in SMAN 10 Padang, namely the low attention of students during the learning process takes place. One of the factors that influenced it was the use of cellphones during the learning process. Students tend to use mobile phones not only to find learning material, but also use it for personal purposes such as replying to messages or playing games. Submission of material by teachers tends to be less interesting and monotonous, to overcome students' lack of attention in learning using PowerPoint. The purpose of this study was to see the effect of using Powerpoint in increasing the learning attention of class X students at SMAN 10 Padang. This type of research is a quasi-experimental design with Randomized Control-Group Posttest Only Design. The population in this study were all tenth grade students of SMAN 10 Padang. The sample in this study were class X students of SMA N 10 Padang Academic Year 2018/2019 and the samples used were students of class X MIA 2 as a control class and X MIA 3 as an experimental class. The instrument used to assess students' attention is the student learning attention assessment sheet filled in by the observer. Based on the results of the study using the t-test it can be concluded that there is an influence of the use of PowerPoint in increasing student learning attention. It was proven that the average attention of the experimental class was higher than the control class.